2020
DOI: 10.1080/10942912.2020.1742736
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of enzymatically prepared resistant starch from maize flour and its use in cookies formulation

Abstract: The current study was aimed to enzymatically modify maize flour by using amylase and pullulanase in combination for increasing the yield of resistant starch type III (EM-RSIII). The enzymatic treatment imparts unique desired physicochemical properties to the maize flour including resistant starch content, amylose content, milk, oil, and water interaction ability. The sensory analysis was performed by distributing questioners among individual and results were interpreted by 5-point hedonic scale. Result indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…Likewise, other functional parameters, such as foaming activity, emulsifying activity, swelling power, foam stability, and bulk density followed a similar trend as WAC and OAC compared to control, indicating the prominent role of moth bean flour and xanthan gum addition due to their degree of interaction with water and crystalline structure to take up water (Alamu et al, 2021). These findings were well correlated with previous studies reported on functional properties of maize-based composite flours (Chhabra et al, 2018;Khan et al, 2020;Vidaurre-Ruiz et al, 2019). These results indicated the use of moth bean flour and xanthan gum as a dough characteristics improver as both protein and hydrocolloid increased the functional properties of maize flour blends due to the chemical structure of protein, hydrocolloid, and their interaction with the maize flour.…”
Section: Functional Properties Of Flourssupporting
confidence: 88%
See 1 more Smart Citation
“…Likewise, other functional parameters, such as foaming activity, emulsifying activity, swelling power, foam stability, and bulk density followed a similar trend as WAC and OAC compared to control, indicating the prominent role of moth bean flour and xanthan gum addition due to their degree of interaction with water and crystalline structure to take up water (Alamu et al, 2021). These findings were well correlated with previous studies reported on functional properties of maize-based composite flours (Chhabra et al, 2018;Khan et al, 2020;Vidaurre-Ruiz et al, 2019). These results indicated the use of moth bean flour and xanthan gum as a dough characteristics improver as both protein and hydrocolloid increased the functional properties of maize flour blends due to the chemical structure of protein, hydrocolloid, and their interaction with the maize flour.…”
Section: Functional Properties Of Flourssupporting
confidence: 88%
“…There was a significant difference (p < .05) in the starch and amylose contents of the maize flour blends, which ranged from 67.30%-69.88% to 35.20%-36.95%, respectively. The addition of moth bean flour and xanthan gum collectively affected the amylose content of samples F1-F7 compared to control, which might be linked with debranching of α-(1-6) linkage of amylopectin and depolymerization (Khan et al, 2020). In all, these findings demonstrated the variations in proximate and chemical analyses of maize flour blends by the addition of moth bean flour and xanthan gum, which can be used to improve the quality characteristics of the maize dough.…”
Section: Proximate and Chemical Analysesmentioning
confidence: 73%
“…Currently, RS3 has garnered significant attention in the field of food research and production. Studies on producing RS3 from various foods, including bananas, rice, corn, sago, cassava, peas, wheat, potatoes, etc., have been conducted globally [3][4][5][6][7][8][9][10]. RS3 is characterized by its stable structure and excellent acid and heat resistance [11], making it heat-stable during cooking processes while retaining nutritional functionality.…”
Section: Introductionmentioning
confidence: 99%
“…As reported previously that both exogenous/endogenous proteins have been negatively associated with the hydrolysis of starch by hydrolytic enzymes (amylases, pullulanase) results in reduction of RS contents. [12,13] In addition, Escarpa et al, reported that mixtures of potato starch and albumin during preparation process resulted in decreased of RS yield. At an addition of 5% albumin RS yield reduced by 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improve the production process and understand the mechanism of enzymatic preparation of resistant starch from maize flour, protease pretreatment and adjustment of processing conditions are thus necessary steps. [ 15 ] As, pretreatment contributes a promising role in the preparation process, which was elaborated in our previous paper, [ 12,13 ] and resulted in a significant yield of resistant starch content. Unless this proteinaceous barrier was removed by proteases or other treatments digestion by α‐amylase, amyloglucosidase or/pullulanase was significantly retarded resulting in reduced RS contents in starch.…”
Section: Introductionmentioning
confidence: 99%